2017
DOI: 10.1002/pssa.201700235
|View full text |Cite
|
Sign up to set email alerts
|

The effect of YSi2 nanoinclusion on the thermoelectric properties of p‐type SiGe alloy

Abstract: Corresponding author: email psupree@kk.ac.th, Phone: þ66 87 373 11 22, Fax: þ66 43 203 359 In this research, the p-type Si 80 Ge 20 B 3 alloys composited with YSi 2 nanoinclusions were fabricated by melting spinning and then, spark plasma sintering. The metallic Y was chosen as the source of YSi 2 nanoparticles. It was found that the fully dense nanocomposites were formed with the homogeneous distribution of YSi 2 nanoinclusions in the SiGe matrix. The thermoelectric measurement showed that YSi 2 addition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…SiGeAu samples exhibited a 1.4 times higher S value and the resultant twice higher S 2 σ at the same σ than SiGe samples without Au. Furthermore, as shown in Figure d where previously reported results of single crystals and polycrystals of SiGe with various Ge fraction (10–80%), RTG SiGe, nanostructured SiGe, modulation-doped SiGe, and SiGe-YSi 2 nanocomposites are plotted, , it was found that in our present SiGeAu samples where just a small amount of Au (2 at. %) was introduced into the SiGe material, the highest S 2 σ value of 22 μW cm –1 K –2 at RT was achieved among many other SiGe-related materials that have ever been reported.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…SiGeAu samples exhibited a 1.4 times higher S value and the resultant twice higher S 2 σ at the same σ than SiGe samples without Au. Furthermore, as shown in Figure d where previously reported results of single crystals and polycrystals of SiGe with various Ge fraction (10–80%), RTG SiGe, nanostructured SiGe, modulation-doped SiGe, and SiGe-YSi 2 nanocomposites are plotted, , it was found that in our present SiGeAu samples where just a small amount of Au (2 at. %) was introduced into the SiGe material, the highest S 2 σ value of 22 μW cm –1 K –2 at RT was achieved among many other SiGe-related materials that have ever been reported.…”
Section: Resultssupporting
confidence: 69%
“…There are many reports of SiGe-based thermoelectric materials. It is known that SiGe exhibits lower κ (∼6 W m –1 K –1 ) due to alloy scattering than bulk Si. ,, As for the studies about the SiGe-based films containing Au, some reported the anomalous enhancement of S 2 σ, , and others reported no enhancement of S 2 σ . This difference is scientifically and practically interesting, and it comes from the unclearness of S 2 σ enhancement mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In SiGe alloys, the large difference in the mean free path between electron (approximately 5 nm) and phonon (approximately 200–300 nm) contributions leads to a strong influence of nanostructuring in a range of 10–100 nm, which reduces the thermal conductivity without significantly reducing the electrical conductivity [ 182 ]. Therefore, nanostructuring [ 183 , 184 , 185 ] and the use of nanoinclusions [ 184 , 186 , 187 , 188 , 189 ] are common strategies to further improve the thermoelectric properties of SiGe alloys. For preparation of SiGe alloys, solid-state ball milling [ 180 , 183 , 186 , 187 , 190 , 191 , 192 , 193 , 194 ] or melt spinning (MS) [ 182 , 189 ] in combination with subsequent SPS are commonly used.…”
Section: Metals and Intermetallicsmentioning
confidence: 99%
“…Therefore, nanostructuring [ 183 , 184 , 185 ] and the use of nanoinclusions [ 184 , 186 , 187 , 188 , 189 ] are common strategies to further improve the thermoelectric properties of SiGe alloys. For preparation of SiGe alloys, solid-state ball milling [ 180 , 183 , 186 , 187 , 190 , 191 , 192 , 193 , 194 ] or melt spinning (MS) [ 182 , 189 ] in combination with subsequent SPS are commonly used. Bathula et al [ 192 ] reported a peak zT of 1.72 with a power factor of 28.7 W cm −1 K −2 for n -doped Si 80 Ge 20 with SiC nanoinclusions.…”
Section: Metals and Intermetallicsmentioning
confidence: 99%
“…Silicon germanium (SiGe) has been attracted attention as one of the promising thermoelectric materials due to its non-toxicity, chemical stability, and high ZT in the high temperature range [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. However, SiGe does not have high ZT near room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%